Achieving SDG-16 in State Owned Enterprise by Implementation of ISO 37001: Anti-Bribery Management - Nur'Asih Budhi Dharma Putri; Ampuan Situmeang; Triana Dewi Seroja (Universitas Internasional Batam, 2024)
In 2021, SOEs Minister Erick Thohir launched the AKHLAK program to address SOEs problems including corruption cases. Indonesia as a member of the UN has an agenda to achieve, which is Sustainable Development Goals (SDGs). The high number of corruption cases in SOEs slows down the achievement of SDGs, especially no. 16